Simulator development of industrial process of normal alkanes c9-c14 dehydrogenation using methods of quantum chemistry; Petroleum and Coal; Vol. 52, № 2 - Frantsina E. V.; Afanasjeva J. I.; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N.; Kravtsov А. V. Anatoly Vasilyevich; Zuev V. A.; Kozlov I. A.; Milishnikov A. V. (2010, 2010)
Based on mathematical approach method, computer modeling system was applied to higher alkanes dehydrogenation process optimization. Use of the system allows determination of the optimal technological characteristics; calculation of process characteristics taking into account feed composition,technological conditions and type of catalyst